Evaluation of Balance Exercises on Balance, Fall Risk, and Quality of Life in Postmenopausal Women - Samed Solak; Hilal Yeşil; Ümit Dündar; Hasan Toktaş; Murat Yeşil; Murat Korkmaz (Galenos Yayinevi, 2022)
Objective:This study, it was investigated the effectiveness of proprioceptive neuromuscular facilitation and Frenkel exercises on balance, fall risk and quality of life in postmenopausal women.Materials and Methods:Forty-eight postmenopausal women were randomized to proprioceptive neuromuscular facilitation (n=24) and Frenkel (n=24) exercise groups (in the form of a home exercise program). Before the study and at the fourth week after the study, all participants were evaluated for handgrip- strength, quality of life, risk of falling, and balance (functional reach test, one leg stand test, timed up and go test, and Berg balance scale).Results:Significant improvement was achieved in all evaluation parameters in the proprioceptive neuromuscular facilitation group (p<0.05). In the Frenkel group, significant improvement was observed in all evaluation parameters (p<0.05), except for the one-leg stand test (p=0.064) and the short form-36 mental health score (p=0.057). It was observed that there was no significant difference between the two groups in the scores of handgrip strength, functional reach test and timed up and go test (p>0.05).Conclusion:Proprioceptive neuromuscular facilitation and Frenkel exercises had significant effects on balance parameters, fall risk and quality of life in postmenopausal women. Frenkel exercise program is cheaper and requires less labor, therefore, we think that it may be preferable in terms of improving balance and reducing the risk of falling in postmenopausal women.